The validation of the Norwegian Basic Psychological Need Satisfaction and Frustration Scale: A stratified sampling procedure - van der Kaap-Deeder, Jolene; Sanchez, Alba; Johannessen, Maria Regine Aasland; Stenseng, Frode; Saksvik-Lehouillier, Ingvild; Heissel, Andreas (Frontiers in Psychology, 2022)
This study aimed to validate the Norwegian version of the Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS) and to examine its relations with indicators of well-being and ill-being. Additionally, despite the vast number of studies employing the BPNSFS, norms related to the BPNSFS are currently lacking. Therefore, we also aimed to provide normative data for this scale. Data were collected among a representative sample of 326 participants (Mage = 42.90 years, SD = 14.76; range 18-70) in Norway, of which 49.7% was female. Results yielded evidence for a six-factor structure (i.e., combining satisfaction/frustration with the type of need) and showed the subscales to be highly reliable. Subsequent structural equation modeling showed that both need satisfaction and need frustration related strongly to vitality, life satisfaction, and internalizing symptoms, but in opposite ways. Norm scores were provided, thereby differentiating between women and men and different age groups. These findings support the use of the Norwegian BPNSFS and provide researchers and professionals with normative data on the most widely used tool to assess individuals’ satisfaction and frustration of the basic psychological needs for autonomy, competence, and relatedness.